Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11187-009-9182-x
|View full text |Cite
|
Sign up to set email alerts
|

Is the R&D behaviour of fast-growing SMEs different? Evidence from CIS III data for 16 countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
137
1
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 32 publications
(22 reference statements)
15
137
1
16
Order By: Relevance
“…Schreyer (2000: 25), in a study covering six European countries, notes that "all the existing evidence points in the same direction: high-growth firms are more technology intensive than the average firm." Hölzl (2009), moreover, finds that in countries closer to the technological frontier, HGFs have a higher R&D intensity than non-HGFs. Further, in a least squares regression framework, Stam and Wennberg (2009) demonstrate that R&D has a positive effect on growth for the top 10 percent of fastest growing startups, but this is not the case for the overall population of firms.…”
Section: Innovation Activities Firm Growth and Hgfsmentioning
confidence: 98%
See 2 more Smart Citations
“…Schreyer (2000: 25), in a study covering six European countries, notes that "all the existing evidence points in the same direction: high-growth firms are more technology intensive than the average firm." Hölzl (2009), moreover, finds that in countries closer to the technological frontier, HGFs have a higher R&D intensity than non-HGFs. Further, in a least squares regression framework, Stam and Wennberg (2009) demonstrate that R&D has a positive effect on growth for the top 10 percent of fastest growing startups, but this is not the case for the overall population of firms.…”
Section: Innovation Activities Firm Growth and Hgfsmentioning
confidence: 98%
“…Therefore, it is perhaps not surprising that previous empirical studies on the industry distribution of HGFs paint a rather ambiguous picture. Early research found evidence of a link between technology and firm growth (Storey 1991(Storey , 1994Kirchoff 1994), and a number of more recent studies have found indications of a positive association between high-tech status or R&D intensity and HGFs (Schreyer 2000;Delmar et al 2003;Hölzl 2009;Wennberg 2009). Schreyer (2000: 25), in a study covering six European countries, notes that "all the existing evidence points in the same direction: high-growth firms are more technology intensive than the average firm."…”
Section: Innovation Activities Firm Growth and Hgfsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely motivated by the fact that the literature on gazelles emphasizes that the bulk of their economic contribution is due to the process of creative destruction that they are able to engender. Within this line of reasoning, the net job creation ascribed to high growth firms stems from an endless dynamics process in which new opportunities emerge and are likely to replace obsolete activities (Hölzl, 2009(Hölzl, , 2010Henrekson and Johansson, 2010;Daunfelt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…elképzelhető, hogy bizonyos iparágakban gyorsabb növekedés jellemző, de az is lehetséges, hogy egyes cégek kiugróan magas növekedésre képesek átlagos vagy alacsony növekedéssel jellemzett iparágakban (Hölzl [2009], Falkenhall-Junkka [2009], Bastesen-Vatne [2009], Henrekson-Johansson [2010]). egyes eredmények alátámaszt-ják a hálózatosodás és az együttműködések jótékony hatását, míg mások ezt megcáfol-ják (Brüderl-Preisendörfer [1998], Havnes-Senneseth [2001], Lechner-Dowling [2003], Schoonjans és szerzőtársai [2013]).…”
unclassified